2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319647
|View full text |Cite
|
Sign up to set email alerts
|

A single element 3D ultrasound tomography system

Abstract: Over the past decade, substantial effort has been directed toward developing ultrasonic systems for medical imaging. With advances in computational power, previously theorized scanning methods such as ultrasound tomography can now be realized. In this paper, we present the design, error analysis, and initial backprojection images from a single element 3D ultrasound tomography system. The system enables volumetric pulse-echo or transmission imaging of distal limbs. The motivating clinical applications include: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…5 The presented flexible single element system will support future development and validation of new algorithms. 4 Future work on the system will include: B-mode/UST imaging of additional phantom and in-vivo targets, volumetric reconstruction of scanned geometries, robust segmentation of layers and volumes, and integration of ultrasound imaging into the prosthetic design work-flow. Results and insights gained from the projected work will inform and guide future clinical system designs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 The presented flexible single element system will support future development and validation of new algorithms. 4 Future work on the system will include: B-mode/UST imaging of additional phantom and in-vivo targets, volumetric reconstruction of scanned geometries, robust segmentation of layers and volumes, and integration of ultrasound imaging into the prosthetic design work-flow. Results and insights gained from the projected work will inform and guide future clinical system designs.…”
Section: Discussionmentioning
confidence: 99%
“…We have expanded upon the data set collected previously on the system and demonstrated that the capability of collecting in-vivo data. 4 Leveraging the flexibility of the designed system, multiple frequency transducers have been tested on three separate subjects with a total of five image targets. Comparisons of B-mode versus MRI scans of each target are presented and show congruence between the two imaging modalities for the each limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, breast ultrasound relies heavily on the doctor's interpretation and is often used as a supplementary tool [13,14]. In general, biopsy is the gold standard for the diagnosis of breast cancer, which show that there are a lot of false-positive cases diagnosed by ultrasound imaging [15][16][17][18]. Ultrasound computer tomography (USCT) is a potential candidate for the imaging of breast cancer [19,20].…”
Section: Introductionmentioning
confidence: 99%